Spinal Anesthesia Using Low Concentration Hypobaric Bupivacaine For Ano-Rectal Surgery. A Randomized Controlled Trial - VASUDEVAN JAGANNATHAN; UMESHKUMAR ATHIRAMAN; MEENA NATHAN CHERIAN (International Journal of Pharma and Bio Sciences, 2011)
Background: To study the efficacy of spinal analgesia with low concentration bupivacaine for anorectal surgery as compared to low dose bupivacaine epidural analgesia. Methods: This randomized control study was conducted on 60 adult patients undergoing elective anorectal surgery. The patients were randomly allocated into one of three groups of 20 patient’s each. The two treatment arms received spinal analgesia with 0.1% bupivacaine or 0.083% bupivacaine, respectively whereas the control arm received epidural analgesia with 0.375% bupivacaine. The primary outcome measure monitored was preservation of sphincter tone. A number of other variables were monitored including: time taken to perform spinal or epidural analgesia; onset time of the sensory block and upper level of the sensory block; extent of motor block; and adequacy of analgesia. Complications during the intraoperative period and during the first 24 hours post-operatively were also recorded. Comparison of the outcome variables in the three groups was made using appropriate statistical analysis. Results: Sphincter tone was preserved in19 patients in group 2 compared to 15 in group1 and 11 in group 3. All patients in groups 1 and 2 had adequate intraoperative analgesia whereas 4 in group 3 needed supplementation with general anesthesia through mask. The time taken to perform the spinal procedure is shorter than the epidural procedure and the onset time of the sensory blockade for the spinal groups was shorter than the epidural group. No major complications were observed in any group. Conclusions: Low concentration spinal analgesia using 0.1% or 0.083% bupivacaine provides selective sensory blockade with good preservation of sphincter tone and is a good alternative to low dose bupivacaine 0.375% epidural analgesia for the anorectal surgeries.